Study of the hadron calorimeters response for CBM and BM@N experiments at hadron beams. (October 2020) - Karpushkin, N; Finogeev, D; Golubeva, M; Guber, F; Ivashkin, A; Izvestnyy, A; Morozov, S
Abstract: The results of beam tests of the hadron calorimeter with transverse and longitudinal segmentation and with the micropixel photodetectors light readout performed at CERN T9 and T10 beamlines in proton momentum range 2-10 GeV/c are shown. The new signal processing technique based on the waveform fitting of calorimeter signals using the Prony least squares method is proposed. This technique allows to identify weak signals comparable to the level of electronic noise, which is important for performing a muon calibration of calorimeter sections. For the energy calibration of the hadron calorimeter sections with cosmic muons, a new approach that uses the reconstruction of the muon track in the calorimeter is proposed.